Impact of preoperative biliary drainage on postoperative complications and prognosis after pancreaticoduodenectomy: A single-center retrospective cohort study - Wang, Dong; Lin, Huajun; Guan, Chengjian; Zhang, Xiaodong; Li, Peixin; Xin, Chenglin; Yang, Xiaobao; Feng, Zhewen; Min, Yiyang; Gu, Xiaozhe; Guo, Wei (Frontiers in Oncology, 2022)
Background and objectives Obstructive jaundice is common in patients with pancreaticobiliary malignancies. This study aimed to evaluate this impact among patients with malignancies treated with pancreaticoduodenectomy. Methods This retrospective study examined the clinical and follow-up prognostic data of 160 patients with pancreaticobiliary malignancies who underwent pancreaticoduodenectomy (PD) at Beijing Friendship Hospital, Capital Medical University, from January 2016 to July 2020. Outcomes were compared between patients who underwent PBD (PBD group) and those who did not (control group). Postoperative complications were classified according to the Clavien-Dindo classification system. The effects of PBD and biliary drainage efficiency on postoperative complications were evaluated using the chi-square test. The Kaplan-Meier analysis was used for between-group comparison of survival prognosis. Results There were total 160 patients enrolled. PBD was performed in 90 of the 160 patients, with PBD performed using an ERCP approach in 55 patients and with PTC used in the remaining 35 cases. The mean duration of drainage in the PBD group was 12.8 ± 8.8 days, with a reduction of 44.77 ± 28.11% in total bilirubin level and 47.95 ± 30.59% in direct bilirubin level. The overall rate of complications was 48.05% (37/77) in the control group and 65.55% (59/90) in the PBD group, a non-significant difference (χ2=3.527, p=0.473). The C-reactive protein to albumin ratio (CAR) on the third postoperative day was higher in the PBD group than in the control group (between-group difference=0.94, p=0.043). The overall rate of postoperative complications was significantly higher among patients who underwent PBD for >2 weeks (χ2=6.102, p=0.013), with the rate of severe complications also being higher for this subgroup of PBD patients (χ2=4.673, p=0.03). The overall survival time was 47.9±2.45 months, with survival being slightly lower in the PBD group (43.61±3.26 months) than in the control group (52.24±3.54 months), although this difference was not significant (hazard ratio (HR)=0.65, p=0.104). Conclusion In patients with malignant biliary obstruction, PBD does not affect the incidence of postoperative complications after pancreaticoduodenectomy nor does it affect patient survival. Prolonged biliary drainage (>2 weeks) may increase the incidence of overall postoperative complications and severe complications.